D-band surface-wave modulator and signal source with 40 dB extinction ratio and 3.7 mW output power in 65 nm CMOS - Liang, Yuan (2020)
High extinction ratio (ER) modulator and high output power source are demonstrated in 65 nm CMOS by generating the surface-wave at D-band. By introducing sub-wavelength periodic corrugation structure, surface plasmon polariton (SPP) is established to propagate TM-mode signal with strongly localized surface-wave, significantly reducing the radiation loss at sub-THz. A high-Q surface-wave resonator is formed by periodically drilling grooves onto split ring resonator (SRR) unit-cells with interleaving placement. Modulation is realized by tuning the inner ring of the stacked SRR. A four-ways power combined fundamental 80 GHz coupled-oscillator-network (CON) is realized by incorporating the surface-wave resonator unit-cell, which is frequency doubled to 160 GHz. Measured results show that modulator achieves the best isolation and ER under the smallest area, and the proposed CON achieves high power efficiency and power density.